Hydrogeochemistry and Groundwater Quality Index in Hong and Environs, Adamawa State, North Eastern Nigeria - Ankidawa, Buba Apagu; Ishaku, Jackson M; Bello, Y (International Journal of Integrated Engineering, 2017)
This research is aimed at understanding the hydrogeochemical processes and groundwater quality index (GWQI) in Hong area and environs, north eastern, Nigeria. Fifteen groundwater samples were collected and analyzed chemically and bacteriologically using spectrophotometric, titrimetric and membrane filtration methods. Analytical results indicated that the groundwater in the area is acidic, fresh and moderately hard. The order of abundance of the cations were in Na+